Histamine induced changes in breathing pattern may precede bronchoconstriction in selected patients with bronchial asthma. Issue 7 (July 1994) - Fanelli, A; Duranti, R; Gorini, M; Spinelli, A; Gigliotti, F; Scano, G
Abstract : BACKGROUND--In asthmatic patients methacholine or histamine challenge may result in more rapid and shallow breathing. Bronchoconstriction can also be associated with changes in the pattern of breathing. However, few studies, particularly in patients with asthma, have investigated the possibility that changes in the pattern of breathing may precede the onset of bronchoconstriction. METHODS--Eight subjects were selected from 34 consecutive asthmatic patients who had previously exhibited a significant increase in respiratory frequency (Rf) and decrease in tidal volume (VT) accompanying a 20% or greater fall in FEV1 during a histamine bronchial provocation test. These patients also had bronchial hyperresponsiveness (histamine PC20FEV1 0.1-0.25 mg/ml). VT, Rf, and the ratio of VT to Rf were evaluated breath by breath under control conditions and two minutes after inhalation of either saline or each of a series of progressively increasing concentrations of histamine. In each subject the coefficient of variation (CV) for each breathing pattern variable was calculated under control conditions and at each histamine concentration over at least 30-40 breaths. For FEV1, VT and Rf step by step coefficients of variation were averaged and the mean (2SD) CV was considered to represent a threshold value in each patient. RESULTS--Histamine challenge resulted in increased Rf and Rf/VT, and decreased VT and FEV1. In all but one subject change in Rf and Rf/VT beyond the threshold value preceded change in FEV1 beyond the threshold value. The threshold concentrations of histamine for Rf and Rf/VT did not correlate with the threshold value for FEV1. CONCLUSIONS--In selected asthmatic patients a change in breathing pattern occurs prior to a change in FEV1. These results suggest that narrowing of the airways, in terms of decrease in FEV1, does not play a major part in the initial change in the pattern of breathing. This may be caused by direct stimulation of vagal airway receptors.